Analisis Rasio Kepatuhan Wajib Pajak Orang Pribadi Atas Pelaporan Surat Pemberitahuan Tahunan Pajak Penghasilan Pada Kantor Pelayanan Pajak Pratama Maumere - Reve, Maria Supriyati Evantris; Tanusi, Gabriel; Langga, Lambertus (Program Studi Manajemen Universitas Flores, 2021)
The purpose of this study was to determine the level of taxpayer compliance Individuals in reporting the Annual Income Tax Returns and to find out the efforts in optimizing the receipt of letter reporting Annual Income Tax Notice at the Primary Tax Office Maumere. This research is quantitative descriptive. This research implemented at the Maumere Primary Tax Service Office. Data collection using the method of documentation, interviews and literature study. Technique data analysis used descriptive quantitative using ratios, yang including: Income Tax received and Letter Reporting Compliance ratio Timely Income Tax Annual Notice. The results of this study indicate that the level of compliance of individual taxpayers Personal in reporting the Annual Income Tax Return is seen from (1) the ratio Compliance with the reporting of the Annual Income Tax Return can be categorized less compliant with an average of 48.98%, (2) Letter Report Compliance ratio. The on-time Annual Income Tax Period shows the average below 60% namely 4.681%.